New KCNN4 Variants Associated With Anemia: Stomatocytosis Without Erythrocyte Dehydration - Allegrini, B.; Jedele, S.; David Nguyen, L.; Mignotet, M.; Rapetti-Mauss, R.; Etchebest, C.; Fenneteau, O.; Loubat, A.; Boutet, A.; Thomas, C.; Durin, J.; Petit, A.; et al. (Frontiers in Physiology, 2022)
The K+ channel activated by Ca2+, KCNN4, has been shown to contribute to red blood cell dehydration in the rare hereditary hemolytic anemia, the dehydrated hereditary stomatocytosis. We report two de novo mutations on KCNN4, substituting either V222L or H340N amino acids characterized at the molecular, cellular and clinical level. Whereas both mutations were shown to increase the calcium sensitivity of the K+ channel, leading to channel opening for lower calcium concentration compared to WT KCNN4 channel, there was no obvious red blood cell dehydration in patients carrying one or the other mutation. The clinical phenotype was greatly different between carriers of the mutated gene ranging from severe anemia for one patient to a single episode of anemia for the other patient or no documented sign of anemia for the parents who also carried the mutation. These data compared to already published KCNN4 mutations question the role of KCNN4 gain-of-function mutations in hydration status and viability of red blood cells in blood stream.